Precious metal catalyst and its preparation method and application

The Ru-Co3O4 catalyst prepared by electrochemical deposition atom doping method solves the problem of insufficient activity and stability of existing precious metal catalysts in acidic OER, and achieves the improvement of efficient catalytic performance and cost reduction, with good application prospects.

CN117737784BActive Publication Date: 2025-02-14LANZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310028280.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2025-02-14
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

Existing precious metal catalysts are insufficient in redox reactions (OERs) in acidic environments, and are expensive, so they cannot be widely used on a large scale.

Method used

The electrochemical deposition atom doping method is used to accurately regulate the crystallographic combination form of precious metals and non-precious metals, and a tetrahedral site-doped Ru-Co3O4 catalyst is prepared to optimize the electronic structure to improve catalytic performance while saving the amount of precious metals and reducing costs.

Benefits of technology

It has achieved the improvement of efficient catalytic performance in acidic OER, while reducing the amount and cost of precious metals, and has good application prospects in proton exchange membrane water electrolysis system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117737784B_ABST
    Figure CN117737784B_ABST
Patent Text Reader

Abstract

The present invention discloses a noble metal catalyst and a preparation method and application thereof. The noble metal catalyst comprises a substrate and an active component supported on the substrate, wherein the active component comprises ruthenium-doped cobalt tetraoxide. The noble metal catalyst of the present invention can save the amount of noble metal used and thus reduce the cost while optimizing the electronic structure and improving the catalytic performance, and has good application prospects in a proton exchange membrane water electrolysis system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical catalysis, and in particular relates to a noble metal catalyst, a preparation method thereof, and an application thereof in electrocatalytic water decomposition. Background Art

[0002] Hydrogen energy is a secondary energy source with abundant sources, green and low carbon, and wide applications. It can help to absorb renewable energy on a large scale, realize large-scale peak load regulation of power grids, and cross-seasonal and cross-regional energy storage, and accelerate the low-carbonization of industries, construction, transportation, etc. Among them, the proton exchange membrane (PEM) water electrolysis method in an acidic environment is considered to be an important technology for achieving large-scale hydrogen production.

[0003] An important part of water electrolysis technology is the study of electrocatalysts. The anode working area, namely the anode oxygen evolution reaction (OER) part, consumes the most energy in water electrolysis. In the field of acidic OER catalyst research, non-precious metal OER catalysts are limited by low activity and stability. Traditional precious metal catalysts such as ruthenium dioxide (RuO2) and iridium dioxide (IrO2) have low reserves and high prices on the one hand, and their catalytic performance needs to be improved on the other hand, so they cannot be widely used on a large scale. It is necessary to develop new acidic OER catalysts to meet the challenges of high current density and high acidity of modern PEM water electrolysis equipment. Summary of the invention

[0004] In order to solve one of the above-mentioned technical problems existing in the prior art, the present invention prepares an atomic substitution type high-efficiency acidic OER precious metal catalyst with excellent performance. The catalyst adopts an electrochemical deposition atomic doping method to accurately control the crystallographic bonding form of precious metals and non-precious metals, and obtains a tetrahedral site-doped Ru-Co3O4 catalyst. While optimizing the electronic structure and improving the catalytic performance, it can save the amount of precious metals and thus reduce costs.

[0005] A first aspect of the present invention provides a noble metal catalyst, which comprises a substrate and an active component supported on the substrate, wherein the active component comprises ruthenium and cobalt oxide, and the cobalt oxide is a spinel structure.

[0006] In some embodiments, the active component is ruthenium-doped cobalt tetroxide.

[0007] In some embodiments, the ruthenium is doped at the tetrahedral sites of the spinel structure.

[0008] In some embodiments, in the active component, the molar ratio of ruthenium to cobalt is (2-50):100, for example, 2:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 40:100, 50:100 or any value therebetween. In some preferred embodiments, in the active component, the molar ratio of ruthenium to cobalt is (3-30):100, more preferably (10-25):100. In a further preferred embodiment, in the active component, the molar ratio of ruthenium to cobalt is (20-25):100.

[0009] In some embodiments, in the catalyst, the loading amount of ruthenium element on the substrate is 0.1-0.5 mg / cm 2 , for example 0.1 mg / cm 2 , 0.2mg / cm 2 , 0.3mg / cm 2 , 0.4mg / cm 2 , 0.5mg / cm 2 Or any value therebetween, preferably 0.2-0.4 mg / cm 2 , more preferably 0.3-0.4 mg / cm 2 .

[0010] In some embodiments, in the catalyst, the loading amount of cobalt element on the substrate is 0.2-5 mg / cm 2 , for example 0.2 mg / cm 2 , 0.5mg / cm 2 , 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 Or any value therebetween, preferably 0.5-4 mg / cm 2 , more preferably 0.5-2.5 mg / cm 2 , more preferably 0.6-1.2 mg / cm 2 .

[0011] In some embodiments, the substrate is a conductive substrate. According to some embodiments, the substrate is selected from one or more of carbon cloth and carbon paper. The carbon cloth and carbon paper used in the present invention are conductive substrates woven from carbon fibers. In some embodiments, the substrate is carbon cloth, and in some embodiments, the substrate is carbon paper.

[0012] A second aspect of the present invention provides a method for preparing a noble metal catalyst, the method comprising electrochemically depositing a deposition solution containing a ruthenium source and a cobalt source on a substrate.

[0013] In some embodiments, the molar ratio of the ruthenium source to the cobalt source is 1:(1-5) based on the ruthenium element and the cobalt element, for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or any value therebetween. In some preferred embodiments, the molar ratio of the ruthenium source to the cobalt source is 1:(1.5-4) based on the ruthenium element and the cobalt element. In a further preferred embodiment, the molar ratio of the ruthenium source to the cobalt source is 1:(2-3) based on the ruthenium element and the cobalt element.

[0014] In some embodiments, the ruthenium salt is selected from one or more soluble ruthenium salts, preferably one or more selected from potassium chlororuthenate, ruthenium trichloride, ruthenium nitrosyl nitrate or ruthenium acetylacetonate.

[0015] In some embodiments, the cobalt source is selected from one or more soluble cobalt salts, preferably one or more cobalt nitrate, cobalt chloride or cobalt sulfate.

[0016] In some embodiments, the substrate is a conductive substrate. According to some embodiments, the substrate is selected from one or more of carbon cloth and carbon paper. The carbon cloth and carbon paper used in the present invention are conductive substrates woven from carbon fibers. In some embodiments, the substrate is carbon cloth, and in some embodiments, the substrate is carbon paper.

[0017] In some embodiments, the molar concentration of the ruthenium source in the deposition solution is 0.01 mol / L to 0.1 mol / L, for example, 0.01 mol / L, 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.08 mol / L, 0.1 mol / L or any value therebetween.

[0018] In some embodiments, the molar concentration of the cobalt source in the deposition solution is 0.05 mol / L to 0.2 mol / L, for example, 0.05 mol / L, 0.075 mol / L, 0.1 mol / L, 0.125 mol / L, 0.15 mol / L, 0.175 mol / L, 0.2 mol / L or any value therebetween.

[0019] In some embodiments, the voltage of the electrochemical deposition is -0.5 V to -2 V, preferably -1 V to -1.5 V. In some specific embodiments, the voltage of the electrochemical deposition is -0.6 V, -0.8 V, -1.0 V, -1.2 V, -1.5 V, -2.0 V, -3.0 V or any value therebetween.

[0020] In some embodiments, the electrochemical deposition time is 10 min-90 min, preferably 20 min-60 min. In some specific embodiments, the electrochemical deposition time is 10 min, 30 min, 50 min, 70 min, 90 min or any value therebetween.

[0021] In some embodiments, the electrochemical deposition uses a three-electrode system.

[0022] In some embodiments, in the three-electrode system, the working electrode is selected from the substrate, the reference electrode is selected from the Ag / AgCl electrode, and the counter electrode is selected from the platinum sheet electrode.

[0023] In some embodiments, the method further comprises performing a high temperature annealing treatment on the electrochemically deposited substrate.

[0024] In some embodiments, the high temperature annealing treatment includes first heating at a heating rate of 1-5 K / min, maintaining for 1-5 hours, and then cooling at a cooling rate of 80-120 K / h.

[0025] In some embodiments, the high temperature annealing treatment includes maintaining at a temperature of 200°C-700°C (e.g., 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, or any value therebetween) for 0.5h-3h (e.g., 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, or any value therebetween). In some preferred embodiments, the high temperature annealing treatment includes maintaining at a temperature of 200°C-400°C for 1h-3h.

[0026] In some embodiments, the method includes setting a program heating and cooling in an air atmosphere for high temperature annealing. In some embodiments, the set program includes a first heating rate to a first temperature; after keeping the temperature at the first temperature for a first time, cooling to a second temperature at a first cooling rate, the program ends, and automatically cools to room temperature to obtain a final product. Preferably, the first heating rate is 1°C / min-5°C / min, preferably 1°C / min-3°C / min. The first temperature is 200°C-700°C, preferably 200°C-400°C. The first time is 0.5-3h, preferably 1-3h. The first cooling rate is 50°C-150°C, preferably 80°C-120°C. The second temperature is 20-150°C, preferably 100°C.

[0027] According to some embodiments of the present invention, the method further comprises pre-treating the substrate before immersing it as a working electrode in a deposition solution containing a ruthenium source and a cobalt source. Preferably, the pre-treatment comprises first immersing it in a mixture of ethanol and an acid solution to treat its surface. In some embodiments, the acid solution may be an organic acid or an inorganic acid selected from one of formic acid, acetic acid or nitric acid, sulfuric acid, and hydrochloric acid. Finally, ultrapure water and ethanol are used to wash away the residual solvent on the surface of the carbon cloth.

[0028] In some embodiments, the method comprises the following steps:

[0029] Step (1): Under a three-electrode system, using a carbon cloth or carbon paper with a hydrophilic surface as a substrate and a deposition solution containing a ruthenium source and a cobalt source as an electrolyte, electrochemical co-deposition is performed to obtain a deposited substrate;

[0030] Step (2): The electrochemically deposited substrate obtained in step (1) is subjected to high-temperature annealing in air to obtain a noble metal catalyst loaded with ruthenium-doped cobalt tetroxide.

[0031] In some specific embodiments, the method for preparing the noble metal catalyst comprises the following steps:

[0032] (1) Electrolyte preparation: Weigh a certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and potassium chlororuthenate hydrate (K2RuCl5·H2O), and use deionized water to prepare a mixed aqueous solution of a certain proportion. The two metal salts are fully mixed and diffused to form a uniform dark solution;

[0033] (2) Pretreatment of the loading substrate: Use activated carbon fiber cloth (referred to as "carbon cloth") as the loading substrate, cut the carbon cloth into appropriate sizes, immerse it in a mixture of concentrated nitric acid and ethanol for hydrophilization, and after the reaction is terminated, wash the residual liquid, and repeatedly perform ultrasonic washing with deionized water and ethanol to obtain a clean carbon cloth stored in deionized water;

[0034] (3) Electrochemical preparation and high-temperature treatment of the catalyst: In an electrochemical three-electrode system, a carbon cloth is used as the working electrode and immersed in an electrolyte. Constant potential deposition conditions are applied to the working electrode to cause an electrochemical reaction on the surface of the carbon cloth carrier, and the cations of the target raw material are deposited on the carrier surface in the form of water and hydroxide. After electrochemical deposition, the obtained catalyst precursor is removed, the residual electrolyte on the carbon cloth is cleaned, and the precursor is placed in a blast oven for drying. Afterwards, the dried precursor is placed in a muffle furnace for high-temperature annealing to obtain the final target catalyst.

[0035] The noble metal catalyst of the present invention adopts an electrochemical deposition atomic doping method to precisely control the crystallographic bonding form of the noble metal and the non-noble metal, thereby obtaining a tetrahedral site-doped Ru-Co3O4 catalyst, which can save the amount of noble metal and thus reduce costs while optimizing the electronic structure and improving the catalytic performance. In addition, the present invention adopts a combined method of electrochemical co-deposition and high-temperature calcination to prepare the noble metal catalyst, which is simple to operate, fast and efficient, and is a method for synthesizing anode catalysts for electrolysis of water with good application prospects.

[0036] The third aspect of the present invention provides the use of the noble metal catalyst described in the first aspect or the noble metal catalyst prepared by the preparation method described in the second aspect in electrocatalytic water decomposition.

[0037] In some embodiments, the noble metal catalyst of the present invention is used for anodic oxygen evolution reaction under acidic conditions.

[0038] The present invention provides a noble metal electrochemical oxygen evolution reaction (OER) catalyst for synthesis and preparation. The catalyst can be applied to the anode working area of ​​an acidic water electrolysis device. Under working conditions, it exhibits a very low overpotential, can greatly reduce the energy consumption of the acidic water electrolysis device in the basic chemical reaction part, achieves an efficient and stable oxygen evolution catalytic effect, has excellent water decomposition catalytic performance, and has good application prospects in proton exchange membrane water electrolysis systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The nanoscale crystal structure, element distribution and catalyst morphology of the catalyst prepared in Example 1 are shown.

[0040] Figure 2 The XPS spectrum of the catalyst prepared in Example 1 is shown.

[0041] Figure 3 The performance comparison of the catalytic current density of the catalyst prepared in Example 1 and the traditional catalyst (RuO2 / Co3O4) is shown.

[0042] Figure 4 A comparison chart of the catalytic properties of catalysts with different Ru contents is shown, where A is the polarization curve (LSV), B is the stability test result (CP), C is the electrochemical active area (Cdl); D is the Tafel slope analysis chart (Tafel), E is the dissolution loss curve, and F is the electrochemical impedance diagram. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0044] Traditional noble metal catalysts are limited by high cost and low atomic utilization. The activity and stability of atomically dispersed electrocatalysts depend largely on the local coordination structure of the metal site, which is directly related to the interaction between electrons and geometric structures. Strong metal-support interactions can promote large electron transfer from metal to neighboring atoms, thereby achieving high acidic OER activity. The present invention combines the advantages of traditional catalysts and loads them for dispersion. Co3O4 with good stability is selected as the design carrier. Combined with the catalytic advantages of the spinel structure, an atomically doped Ru-Co3O4 catalyst is constructed. The strong electronic coupling between the active sites dispersed by Ru atoms and their metal anchoring substrate is successfully achieved to activate the acidic OER activity and improve the solubility resistance of ultra-low ruthenium electrocatalysts.

[0045] The present invention verified the high activity advantage of the catalyst in theory and practice by characterizing the structure of the catalyst itself and studying the catalytic process. The morphology and crystal structure of the catalyst were characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy, and the electrochemical performance of the catalyst was tested by an electrochemical workstation.

[0046] The conductivity of the ultrapure water used in the experiment was 18.25 MΩ, and all reagents used were analytical grade.

[0047] MiniF1ex diffractometer (Rigaku, Japan) was used for X-ray diffraction characterization;

[0048] ApreoS field emission scanning electron microscope (Thermo Fisher Scientific, FEI, USA) was used for catalyst morphology characterization;

[0049] Shanghai Chenhua CHI760E electrochemical workstation is used for cyclic voltammetry, linear sweep voltammetry, chronopotentiometry and chronoamperometry stability tests;

[0050] PT-X platinum electrode clips, platinum sheet electrodes, Ag / AgCl and Hg / Hg2SO4 reference electrodes (Wuhan Gaoshi Ruilian Technology Co., Ltd.) were used for electrodeposition preparation of materials and electrochemical testing;

[0051] Carbon cloth (Fuel Cell Store).

[0052] The loading amounts of ruthenium and cobalt elements were obtained by inductively coupled plasma (ICP-OES) testing.

[0053] Example 1

[0054] 1. Electrolyte preparation: The raw materials are cobalt nitrate hexahydrate Co(NO3)2·6H2O and potassium chlororuthenate hydrate K2RuCl5·H2O. Use a volumetric flask to make a mixed aqueous solution with a Co concentration of 0.1 mol / L and a Ru concentration of 0.05 mol / L.

[0055] 2. Load substrate pretreatment: Cut the carbon cloth into 1.5cm*2.0cm size, immerse it in a mixture of concentrated nitric acid and ethanol for hydrophilization, mix the two in a 1:1 volume ratio, and add liquid until the carbon cloth is submerged. After the reaction stops, wash the residual liquid to obtain a clean carbon cloth stored in deionized water.

[0056] 3. Electrochemical preparation and high-temperature treatment of the catalyst: In the electrochemical three-electrode system, carbon cloth is used as the working electrode, the silver / silver chloride standard electrode is used as the reference electrode, and the platinum electrode is used as the counter electrode. Constant potential deposition conditions are applied to the working electrode: -1.2V (vs Ref), 1800s. After the obtained catalyst precursor is dried, it is placed in a muffle furnace for high-temperature annealing treatment, with a heating rate of 2°C / min, heated to 300°C, maintained for 2h, and a cooling rate of 100°C / h to obtain the final target catalyst (RuCo2-O). After testing, the loading amount of ruthenium element on the carbon cloth substrate in the target catalyst is 0.37mg / cm 2 The loading amount of cobalt on the carbon cloth substrate is 0.91 mg / cm 2 , the molar ratio of ruthenium element to cobalt element is 23.7:100.

[0057] The electron microscopy characterization results of the prepared target catalyst are as follows Figure 1 As shown, the results indicate that the basic structure of the catalyst material is in the form of nanosheets, the nanosheet catalyst material is arranged in an isotropic stacking manner, and the elements are evenly distributed. Figure 2 The XPS spectrum of the target catalyst shows that the chemical environment of Ru in the target catalyst has changed, indicating that the metal-support interaction is achieved in the target catalyst and the Co 2p diagram of Co 2+ Satellite Peak (Co 2+ Sat ) disappeared after Ru doping, indicating that Ru atoms were successfully doped into the tetrahedral metal sites of Co3O4, which optimized the local electronic structure of the catalyst. Compared with RuO2 catalyst and Co3O4 catalyst, the electrochemical linear sweep voltammetry (LSV) test found that the catalytic activity of the target catalyst RuCo2-O was comprehensively improved (such as Figure 3 shown).

[0058] Example 2

[0059] 1. Electrolyte preparation: The raw materials are cobalt nitrate hexahydrate Co(NO3)2·6H2O and potassium chlororuthenate hydrate K2RuCl5·H2O. Use a volumetric flask to make a mixed aqueous solution with a Co concentration of 0.15 mol / L and a Ru concentration of 0.05 mol / L.

[0060] 2. Load substrate pretreatment: Cut the carbon cloth into 1.5cm*2.0cm size, immerse it in a mixture of concentrated nitric acid and ethanol for hydrophilization, mix the two in a 1:1 volume ratio, and add liquid until the carbon cloth is submerged. After the reaction stops, wash the residual liquid to obtain a clean carbon cloth stored in deionized water.

[0061] 3. Electrochemical preparation and high temperature treatment of catalysts: In the electrochemical three-electrode system, carbon cloth is used as the working electrode, the silver / silver chloride standard electrode is used as the reference electrode, and the platinum electrode is used as the counter electrode. Constant potential deposition conditions are applied to the working electrode: -1.2V (vs Ref), 1800s. After the obtained catalyst precursor is dried, it is placed in a muffle furnace for high temperature annealing treatment, with a heating rate of 2°C / min, heated to 300°C, maintained for 2h, and a cooling rate of 100°C / h to obtain the final target catalyst (RuCo3-O). After testing, the loading amount of ruthenium element on the carbon cloth substrate in the target catalyst is 0.39mg / cm 2 The loading amount of cobalt on the carbon cloth substrate is 2.25 mg / cm 2 , the molar ratio of ruthenium element to cobalt element is 10.1:100.

[0062] Example 3

[0063] 1. Electrolyte preparation: The raw materials are cobalt nitrate hexahydrate Co(NO3)2·6H2O and potassium chlororuthenate hydrate K2RuCl5·H2O. Use a volumetric flask to make a mixed aqueous solution with a Co concentration of 0.2 mol / L and a Ru concentration of 0.05 mol / L.

[0064] 2. Load substrate pretreatment: Cut the carbon cloth into 1.5cm*2.0cm size, immerse it in a mixture of concentrated nitric acid and ethanol for hydrophilization, mix the two in a 1:1 volume ratio, and add liquid until the carbon cloth is submerged. After the reaction stops, wash the residual liquid to obtain a clean carbon cloth stored in deionized water.

[0065] 3. Electrochemical preparation and high-temperature treatment of catalysts: In the electrochemical three-electrode system, carbon cloth is used as the working electrode, the silver / silver chloride standard electrode is used as the reference electrode, and the platinum electrode is used as the counter electrode. Constant potential deposition conditions are applied to the working electrode: -1.2V (vs Ref), 1800s. After the obtained catalyst precursor is dried, it is placed in a muffle furnace for high-temperature annealing treatment, with a heating rate of 2°C / min, heated to 300°C, maintained for 2h, and a cooling rate of 100°C / h to obtain the final target catalyst (RuCo4-O). After testing, the loading amount of ruthenium element on the carbon cloth substrate in the target catalyst is 0.27mg / cm 2 The loading amount of cobalt on the carbon cloth substrate is 3.99 mg / cm 2 , the molar ratio of ruthenium element to cobalt element is 3.9:100.

[0066] Examples 1-3 used different Ru / Co feed ratios and used different electrochemical property tests to study the electrochemical performance differences between the optimal catalyst and other catalysts. The results showed that the electrochemical LSV test found that the catalyst prepared in Example 1 had an extremely low overpotential of 155mV (@10mA cm -2 ) and very high catalytic current density (see Figure 4 A), the electrochemical chronopotentiometry (CP) test found that the catalyst can stably maintain catalytic performance for more than 120 hours (see Figure 4 B), and the dissolution loss curve shows that the content of Ru and Co in the solution is almost negligible (see Figure 4 E), further reflecting the realization of metal-support interaction and the optimization of electronic structure. Further electrochemical cyclic voltammetry (CV) test found that the electrochemical active area of ​​the catalyst prepared in Example 1 was as high as 85 mF cm -2 (See Figure 4 C), the Tafel slope in electrochemical kinetics can be calculated by LSV and also shows that Example 1 has the lowest slope, that is, the fastest electrochemical reaction rate (see Figure 4 D), the electrochemical impedance test shows that the materials of Examples 1-3 have the smallest charge transfer resistance (see Figure 4 F).

[0067] From the above series of electrochemical performance test analysis, it can be seen that the noble metal catalyst of the present invention has a more optimized crystal structure and electronic structure. The catalyst of the present invention has a large surface area and a large number of active sites, which make it have good electrocatalytic acidic OER catalytic performance.

[0068] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A noble metal catalyst, comprising a substrate and an active component supported on the substrate, wherein the active component comprises ruthenium and cobalt tetraoxide, the cobalt tetraoxide is a spinel structure, the ruthenium is doped at the tetrahedral site of the spinel structure, the molar ratio of ruthenium element to cobalt element in the active component is (15-30):100, and the substrate is selected from a carbon fiber substrate; The method for preparing the noble metal catalyst comprises electrochemically depositing a deposition solution containing a ruthenium source and a cobalt source on the substrate, and performing a high-temperature annealing treatment on the electrochemically deposited substrate; Calculated on the basis of ruthenium element and cobalt element, the molar ratio of the ruthenium source to the cobalt source is 1:(1-2.5); The ruthenium source is selected from one or more of potassium chlororuthenate, ruthenium trichloride, ruthenium nitrosyl nitrate or ruthenium acetylacetonate; the cobalt source is selected from one or more of cobalt nitrate, cobalt chloride or cobalt sulfate; The voltage of the electrochemical deposition is -1V to -1.5V; the time of the electrochemical deposition is 20min-60min; the electrochemical deposition adopts a three-electrode system; in the three-electrode system, the working electrode is selected from the substrate, the reference electrode is selected from the Ag / AgCl electrode, the counter electrode is selected from the platinum sheet electrode, and the electrochemical deposition is a constant potential deposition; The high temperature annealing treatment includes maintaining the temperature at 200° C.-400° C. for 0.5 h-3 h.

2. The noble metal catalyst according to claim 1, characterized in that In the active component, the molar ratio of ruthenium element to cobalt element is (20-25):

100.

3. The noble metal catalyst according to claim 1 or 2, characterized in that In the catalyst, the loading amount of ruthenium element on the substrate is 0.1-0.5 mg / cm 2 ;or, In the catalyst, the loading amount of cobalt element on the substrate is 0.2-5 mg / cm 2 .

4. The noble metal catalyst according to claim 3, characterized in that In the catalyst, the loading amount of ruthenium element on the substrate is 0.2-0.4 mg / cm 2 Alternatively, in the catalyst, the loading amount of cobalt element on the substrate is 0.5-4 mg / cm 2 .

5. The noble metal catalyst according to claim 3, characterized in that In the catalyst, the loading amount of ruthenium element on the substrate is 0.3-0.4 mg / cm 2 Alternatively, in the catalyst, the loading amount of cobalt element on the substrate is 0.5-2.5 mg / cm 2 .

6. The noble metal catalyst according to claim 1 or 2, characterized in that The substrate is selected from one or more of carbon cloth and carbon paper, and the carbon cloth and carbon paper are conductive substrates woven from carbon fibers.

7. The noble metal catalyst according to claim 1 or 2, characterized in that The molar concentration of the ruthenium source in the deposition solution is 0.01 mol / L to 0.1 mol / L; or, The molar concentration of the cobalt source in the deposition solution is 0.05 mol / L to 0.2 mol / L.

8. The noble metal catalyst according to claim 1 or 2, characterized in that The high temperature annealing treatment includes maintaining the temperature at 200° C.-400° C. for 1 h-3 h.

9. Use of the noble metal catalyst according to any one of claims 1 to 8 in electrocatalytic water decomposition.

10. The use according to claim 9, characterized in that: The application is the application of the noble metal catalyst in oxygen evolution reaction under acidic conditions.

Citation Information

Patent Citations

  • Preparation method and application of Co3O4-RuO2 composite material

    CN114592210A